2002
DOI: 10.2174/1389450023347713
|View full text |Cite
|
Sign up to set email alerts
|

Purine Signaling and Potential New Therapeutic Approach: Possible Outcomes of NTPDase Inhibition

Abstract: Interest for extracellular nucleotides has increased since the pioneer work of Burnstock in the early seventies. Research on cellular functions modulated by purines and pyrimidines has led to the identification and characterization of the different components of purine signaling, namely purinoceptors and ecto-nucleotidases. Receptors for tri- and diphosphonucleosides, known as P2 nucleotide receptors, are designated either P2Y receptors, for those coupled to G-proteins, or P2X for those which are ligand gated-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 0 publications
2
81
0
Order By: Relevance
“…Recent reports demonstrated that ARL 67156 is a weak competitive inhibitor of NTPDase1, NTPDase3 and NPP1, with K i for the human enzymes of 11± 3, 18± 4 and 12± 3 µM, respectively [17,68]. Another ATP analogue, 8-thiobutyladenosine 5′-triphosphate (8-BuS-ATP), and 1-naphthol-3,6-disulfonic acid (BG0136), appear of interest, but so far they have only been characterised on a NTPDaseactive fraction from bovine spleen membranes [69,70]. In addition, recent evidence indicates that some polyoxometalate anionic complexes inhibit rat NTPDases [71], that a uridine-5′-carboxamide derivative selectively inhibits human NTPDase2 [72] and that a novel monoclonal antibody selectively inhibits human NTPDase3 [73].…”
Section: Inhibitors Of Ectonucleotidasesmentioning
confidence: 99%
“…Recent reports demonstrated that ARL 67156 is a weak competitive inhibitor of NTPDase1, NTPDase3 and NPP1, with K i for the human enzymes of 11± 3, 18± 4 and 12± 3 µM, respectively [17,68]. Another ATP analogue, 8-thiobutyladenosine 5′-triphosphate (8-BuS-ATP), and 1-naphthol-3,6-disulfonic acid (BG0136), appear of interest, but so far they have only been characterised on a NTPDaseactive fraction from bovine spleen membranes [69,70]. In addition, recent evidence indicates that some polyoxometalate anionic complexes inhibit rat NTPDases [71], that a uridine-5′-carboxamide derivative selectively inhibits human NTPDase2 [72] and that a novel monoclonal antibody selectively inhibits human NTPDase3 [73].…”
Section: Inhibitors Of Ectonucleotidasesmentioning
confidence: 99%
“…NTPDases have been described in hepatocytes, epithelial cells of the bile duct system, vascular cells, platelets, lymphocytes, monocytes, and macrophages cells (Gendron et al 2002, Bigonnesse et al 2004, Ivanenkov et al 2005. Eight members of the mammalian NTPDases family have been identified, including six membrane-bound enzymes (NTPDases 1-4, 7, and 8) and two secreted enzymes (NTPDases 5 and 6) (Gendron et al 2002, Bigonnesse et al 2004, Ivanenkov et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Eight members of the mammalian NTPDases family have been identified, including six membrane-bound enzymes (NTPDases 1-4, 7, and 8) and two secreted enzymes (NTPDases 5 and 6) (Gendron et al 2002, Bigonnesse et al 2004, Ivanenkov et al 2005. The phylogenetic tree obtained for the NTPDases family (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations